Seafood: Nutritional Gold for Seniors - McManus, Alexandra; Merga, Margaret (Australasian Medical Journal Pty Ltd, 2010)
Objectives: To conduct a systematic review of published evidence around seafood, health and seniors. Method: Data sources reviewing included: Proquest; PubMed; Science Direct; Taylor and Francis; Cochrane Collaboration; Web of Knowledge and Web of Science. Key search terms included seniors, ageing, fish, seafood, protein, health and various lifestyle conditions. Results: A diet high in marine source Omega-3 poly unsaturated fatty acids affords particular benefits for seniors in a reduced risk of all cause mortality, with the strongest evidence around coronary heart disease and ischemic stroke. Other benefits include reduced inflammation associated with arthritis and delay to onset and slowed progression of dementia and Alzheimer's disease. Conclusion: There is increasing evidence to support the regular seafood consumption (particularly oily fish) as being protective against a number of aged-related health conditions. Seniors should be encouraged to consume 3500mg- 4000mg of marine source Omega-3 PUFAs each week.